2018
DOI: 10.3390/ijms19082384
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of miRNAs in Self-Rooted and Grafted Malus Reveals Critical Networks Associated with Flowering

Abstract: Grafting can improve the agricultural traits of crop plants, especially fruit trees. However, the regulatory networks and differentially expressed microRNAs (miRNAs) related to grafting in apple remain unclear. Herein, we conducted high-throughput sequencing and identified differentially expressed miRNAs among self-rooted Fuji, self-rooted M9, and grafted Fuji/M9. We analyzed the flowering rate, leaf morphology, and nutrient and carbohydrate contents in the three materials. The flowering rate, element and carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…These outcomes are valuable for the purposeful analysis of miRNAs in the facilitation of grafting induced drought tolerance. An et al (2018) conducted a Gene Ontology study which showed that miRNAs which are expressed differentially throughout grafting regulated genes involved in a number of processes, including biosynthesis of cellular compounds and metabolism. Various studies revealed that miRNA172 can travel from source to sink in Nicotiana ( Kasai et al, 2010 ) and that miRNA156 functions as a signal which is mobile through the phloem to affect important traits in potato ( Bhogale et al, 2014 ).…”
Section: Molecular Responses At the Graft Interfacementioning
confidence: 99%
“…These outcomes are valuable for the purposeful analysis of miRNAs in the facilitation of grafting induced drought tolerance. An et al (2018) conducted a Gene Ontology study which showed that miRNAs which are expressed differentially throughout grafting regulated genes involved in a number of processes, including biosynthesis of cellular compounds and metabolism. Various studies revealed that miRNA172 can travel from source to sink in Nicotiana ( Kasai et al, 2010 ) and that miRNA156 functions as a signal which is mobile through the phloem to affect important traits in potato ( Bhogale et al, 2014 ).…”
Section: Molecular Responses At the Graft Interfacementioning
confidence: 99%
“…Grafting is an important way to improve plant growth, stress tolerance, and fruit quality, and has been widely used in commercial horticultural crop production (Zahaf et al, 2012; Liu et al, 2016). The molecular mechanisms regulating plant growth via grafting have been investigated by several groups (Kyriacou et al, 2017), for example using high-throughput sequencing in watermelon (Liu et al, 2013), tomato (Estan et al, 2005), apple (An et al, 2018), and grapevine (Pagliarani et al, 2017). These studies showed that grafting affects differential expression of genes in grafted plants.…”
Section: Discussionmentioning
confidence: 99%
“…Although the two varieties were both grafted to the same rootstock, the relationship of grafting to the differential expression of the HMs was not investigated. An et al (2018) studied the miRNA expression in self-rooted and grafted Fuji apple trees by high-throughput sequencing in relation to flowering rate. Some of them that were differentially regulated in response to grafting (miR156, miR172, miR159, miR171) target genes encoding transcription factors that regulate flower formation, and suggested that there is a regulatory network between miRNAs and mRNAs that is generated by grafting.…”
Section: Graft-induced Transcriptional Reprogramming and Epigenetic Cmentioning
confidence: 99%
“…mRNAs, miRNAs, and proteins can act as potential short- and long-distance signals exerting a regulatory role in the receiving graft partner which impacts scion but also whole plant performance. In grapevine, apple and avocado, miRNA and mRNA molecules as well as induction of transcriptional reprogramming in scions has been associated with physiological and metabolic pathways affecting traits of agronomical relevance ( Cookson et al, 2014 ; Kaja et al, 2015 ; Corso et al, 2016 ; Li et al, 2016 ; Chitarra et al, 2017 ; Pagliarani et al, 2017 ; An et al, 2018 ). Gaining a deeper insight into the molecular mechanisms underlying these processes could direct the development of suitable molecular markers to be used for generating and selecting superior grafts with improved yield, quality, and tolerance to abiotic and biotic stresses.…”
Section: Implications For Crop Improvementmentioning
confidence: 99%